Vitamin C stimulates RNA expression of human gingival fibroblasts proliferation and adhesion in cigarette smokers: An in vitro study - Ruaa Alyami; Fahad Ali Alshehri; Reham Al Jasser; Sameerah Shaheen; Amer Mahmood; Mona Ahmed Elsafadi (Saudi Dental Journal)
Background: Smoking and the severity of periodontal disease have long been associated. In Saudi Arabia, tobacco smoking is rising, contributing to the increased demand for products that counter its detrimental effects. The antioxidant properties of vitamin C (vit C) make it a powerful countermeasure to tobacco toxicity. Observation of these effects on human gingival fibroblasts (hGFs) would suggest use of vitamin C in future dental applications. Aim: To examine the proliferation, adhesion, and expression of extracellular RNA in human gingival fibroblasts extracted from cigarette smokers when compared to never-smokers, in association with vitamin C. Materials and Methods: Human gingival fibroblasts were extracted from Periodontal free sites of healthy adult male participants. Group 1; consisted of Heavy cigarette smokers (n = 1) while group 2 was never-smokers (n = 1). Collected cells were cultured and subcultured in supplemented growth medium. Vitamin C was then induced in the medium at the experimental sixth passage. RNA expression analysis using quantitative reverse transcriptase-polymerase chain reaction was performed to analyze the adhesion, proliferation, and extracellular matrix expression. Results: Expression of the adhesion gene (CD44) in the smoker group was significantly downregulated than never-smoker group (p-value = 0.024). After the induction of vitamin C, the smoker samples showed a significant improvement in their gene expression levels. The extracellular genes involved in this study (COL1A1, LAMA3, and TGFB3) were significantly affected by the smoking status. In addition, the proliferation of MK167 and CCNB1 genes in smokers and never-smokers was increased. Conclusion: Cigarette smoking affects the overall properties of human gingival fibroblasts’ adhesion, proliferation, and extra-cellular matrix formation. Furthermore, the addition of vitamin C affects these cellular properties in a positive manner.